Evaluation of thestatus quoof polyphenols analysis: Part II-Analysis methods and food processing effects - Sanches Silva, Ana; Reboredo-Rodriguez, Patricia; Sanchez-Machado, Dalia I.; Lopez-Cervantes, Jaime; Barreca, Davide; Pittala, Valeria; Nabavi, Seyed Mohammad (Wiley, 2020)
Nowadays due to the concern with the environmental impact of analytical techniques and in order to reduce the ecological footprint there is a tendency to use more efficient and faster procedures that use a smaller amount of organic solvents. Polyphenols have been widely studied in plant-based matrices due to their wide and potent biological properties; however there are no standardized procedures both for sample preparation and analysis of these compounds. The second of a two-part review will carry out a critical review of the extraction procedures and analytical methods applied to polyphenols and their selection criteria over a wide range of factors in relation to commerce-associated, environmental, and economic factors. It is foreseen that in the future the analysis of polyphenols in plant-based matrices includes the use of techniques that allow the simultaneous determination of different subclasses of polyphenols using fast, sophisticated, and automated techniques that allow the minimal consumption of solvents.
Keywords: chromatography; extraction; flavonoid; identification; plant-based food; polyphenol; purification; quantification